Turbulent flows and pollution dispersion around tall buildings using adaptive large eddy simulation (LES) - Aristodemou, Elsa; Mottet, Laetitia; Constantinou, Achilleas; Pain, Christopher Charles (My University, 2020)
The motivation for this work stems from the increased number of high-rise buildings/ skyscrapers all over the world, and in London, UK, and hence the necessity to see their effect on the local environment.We concentrate on the mean velocities, Reynolds stresses, turbulent kinetic energies (TKEs) and tracer concentrations. We look at their variations with height at two main locations within the building area, and downstream the buildings. The pollution source is placed at the top of the central building, representing an emission from a Combined Heat and Power (CHP) plant. We see how a tall building may have a positive effect at the lower levels, but a negative one at the higher levels in terms of pollution levels. Mean velocities at the higher levels (over 60 m in real life) are reduced at both locations (within the building area and downstream it), whilst Reynolds stresses and TKEs increase. However, despite the observed enhanced turbulence at the higher levels, mean concentrations increase, indicating that the mean flow has a greater influence on the dispersion. At the lower levels (Z < 60 m), the presence of a tall building enhanced dispersion (hence lower concentrations) for many of the configurations.
Keywords: Tall buildings; Large eddy simulation; Air pollution dispersion; Turbulence